(untitled) (Veterinary Science, 2018)
In the present paper the possible association between body temperature, glycemia and lacticaemia with the surgical act of sterilization of male and female canines is studied. These variables were chosen since they are known to be modified in the face of stressful events. It is expect d to observed changes in metabolic substrates used by the patient during surgery. The variables of interest were studied in three times (pre and intra-surgical) in male and female canines. Significant decreases in lactate and rectal temperature and a significant increase in blood glucose were detected